Managing the Adoption of Digital Comic Media in Fiqh Learning: Managerial Conditions Shaping Effectiveness in an Islamic Secondary School - Walid Walid; Syamsul Rijal (Universitas Nurul Jadid, 2025)
Digital media now shapes how madrasah teach abstract religious content, yet most studies treat comic-based media as a design problem and overlook how a school actually manages its adoption. This study examines how MA (Madrasah Aliyah, Islamic senior high school) Taman Baru Palenggiyan Kedungdung Sampang manages the use of digital comic media in the Fiqh subject, focusing on both the effectiveness of the practice and the factors that support or hinder it. The research used a qualitative case study design. Data came from in-depth interviews with six purposively selected informants, namely the head of madrasah, the teacher, and four students, and were reinforced through classroom observation and documentation. Analysis followed the interactive model of Miles and Huberman and relied on source triangulation to verify each claim. The findings show that the medium's success depended less on the comic itself than on three managerial conditions working together: leadership provisioning, the teacher's shift toward facilitation, and structured time management. Student participation rose noticeably, though gains in understanding remained uneven because setup time and differences in visual literacy limited some learners. These results imply that madrasahs seeking to benefit from digital media must invest in leadership and instructional management, not merely in the technology, since the medium rewards good management and exposes the cost of its absence.